A legal analysis on the doctrine of ministerial responsibility in commonwealth countries / Mohd Nor Hafidzuddin Yusoff, Nurul Nabila Hasni and Asmarina Sakila Kamarolzaman - Yusoff, Mohd Nor Hafidzuddin; Hasni, Nurul Nabila; Kamarolzaman, Asmarina Sakila (2013)
This research traces the origin and the development of the doctrine of Ministerial Responsibility in Malaysia, United Kingdom, Australia and Canada. Comparison has been made between Malaysia, United Kingdom, Australia and Canada to know the development of the doctrine in order to preserve its dignity and importance as it has its own role and shall be uphold in parliamentary tradition. In Malaysia the development of the doctrine in ensuring answerability and accountability of ministers is not effective as compare to the other commonwealth countries. In United Kingdom, Australia and Canada, the convention on Ministerial responsibility has been properly codified in various codes that provide guidelines for minister in performing their duty and in ensuring the integrity of the minister and the government as a whole. In contrast, in Malaysia there is only guidelines, power and methods of appointment of ministers that is provided in Article 39-43 of Federal Constitution and Ministerial Function Act 1969. The doctrine of ministerial responsibility is very essential and important in parliamentary system. It is necessary for the government to maintain unity for effectiveness and confidence of electoral support. Thus this research will consider the suitability of the code of ministerial conduct that to be adopted in Malaysia.